Development of Digital Pocket Book for Disaster Mitigation Materials Coronavirus Disease 2019 (COVID-19) to Increase Student Resilience to Disasters - Yulia Nurfitri; Rita Retnowati; Muhammad Taufik Awaludin (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2022)
Entering the beginning of 2020 there was an extraordinary phenomenon, namely the outbreak of the Coronavirus Disease (COVID-19) which attacked almost all parts of the country in the world. The COVID-19 pandemic disaster causes mild respiratory infections to severe respiratory infections such as pneumonia and the greatest risk can cause death. Other negative impacts include increasing stress and anxiety in individuals. The individual's capacity to deal with and reduce stress and anxiety can arise from having resilience. Resilience is the resilience possessed by individuals, groups, or communities that allow them to face, prevent, minimize and even eliminate the adverse effects of unpleasant conditions, or even change the conditions that include them into a natural thing to overcome, to overcome. Therefore, students need to have resilience abilities. The importance of increasing student resilience in efforts to mitigate the COVID-19 disaster through education is very necessary because schools are an effective means of conveying information. Submission of learning about the dangers of COVID-19 mitigation can be delivered through a learning process with innovative learning media. Based on the results of observations in one high school in Bogor City, it was found that the level of student resilience was still relatively low, namely 56%. The purpose of this study was to determine the effect of digital pocket books on COVID-19 disaster mitigation materials in increasing student resilience to disasters and to determine the effectiveness of digital pocket books on COVID-19 disaster mitigation materials. The research was conducted using themethod Research and Development using the ADDIE model (analyze, design, development, implementation, evaluation). The population in this study were students of class XI MIPA 2 with a sample of 29 students. The results showed that digital pocket books were able to increase students' resilience to disasters to 69% which was included in the medium category. The effectiveness of learning media has a very effective category which is obtained from the average percentage of student responses of 90% and teacher responses of 84%. Keywords: Digital Pocket Book; COVID-19 Disaster Mitigation, Resilience.